Transformasi tes diagnostik two tier ke four-tier berbasis representasi jamak pada konsep atom dan molekul - Sukaria, Muhammad Ikhsan (Universitas Papua, Manokwari, Indonesia, 2025)
This study aims to transform the two-tier diagnostic test instrument into a four-tier one, determine the validity, reliability, and characteristics of the test items to diagnose misconceptions that occur in the concept of atoms and molecules. This study is a development research using the ADDIE model. This development model consists of 5 stages: 1) Analyse, 2) Design, 3) Develop, 4) Implementation, and 5) Evaluation. The four-tier diagnostic test is a refinement of the two-tier test, which only consists of answers and reasons. The addition of a two-tier to the four-tier diagnostic test includes the level of confidence that indicates the accuracy of the answer choices and the reasons for choosing the answer in tier I. The test items are developed based on multiple representations to make it easier for students to understand the main questions. The study subjects were junior high school students in grade IX who had studied the material on atoms, molecules and ions. The instruments produced include grids, instructions for working on the test, test questions, answer keys, scoring guidelines, and guidelines for interpreting the results. Validity testing by expert validators showed that the developed instrument was valid. The reliability of the developed test was 0.87. Analysis of the test results found five profiles of understanding of the concepts tested: scientific conception, misconception, lack of knowledge, false positive, and false negative from the material tested. The results of applying the four-tier diagnostic test instrument showed that 36.98% experienced misconceptions in the concept of atoms and 34.97% in the concept of molecules. Based on these findings, it can be concluded that the four-tier diagnostic test developed can identify misconceptions in the concepts of atoms and molecules